Enhancing Human Performance: Issues, Theories, and Techniques (1988)
Contents Preface Part I Overview 1 Introduction 2 Findings and Conclusions 3 Evaluation Issues Part II Psychological Techniques 4 Learning 5 Improving Motor Skills 6 Altering Mental States 7 Stress Management 8 Social Processes Part III Parapsychological Techniques 9 Paranormal Phenomena References Appendixes A Summary of Techniques: Theory, Research, and Applications B Background Papers C Committee Activities D Key Terms E Military Applications of Scientific Information F Biographical Sketches Index